(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article examines the strengths and weaknesses of the C++ and Python programming languages, their efficiency and usability for working with lists and arrays. Principles for implementing convenient methods for working with lists are presented.